2010
DOI: 10.1038/sj.bjc.6605595
|View full text |Cite
|
Sign up to set email alerts
|

Oxaliplatin, irinotecan and capecitabine as first-line therapy in metastatic colorectal cancer (mCRC): a dose-finding study and pharmacogenomic analysis

Abstract: BACKGROUND: A dose-finding study was performed to evaluate the dose-limiting toxicity (DLT), maximum-tolerated dose (MTD) and the recommended dose (RD) of escalating the doses of capecitabine and fixed doses of irinotecan and oxaliplatin on a biweekly schedule for metastatic colorectal cancer patients (mCRC). A pharmacogenomic analysis was performed to investigate the association between SNPs and treatment outcome. METHODS: Eighty-seven chemotherapy-naïve mCRC patients were recruited through a two-step study d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 42 publications
4
26
0
Order By: Relevance
“…However, our observation of a nonsignificantly increased OS in carriers of the valine is in accordance with previous reports of an association of the GSTP1 valine allele with increased survival (progression-free survival or OS) in CRC patients in general [7], as well as in patients with metastatic CRC treated with different chemotherapeutic regimens [8--11,13], although the results were significant only in two studies [8,11]. Other studies either found no association overall or decreased survival after chemotherapy in carriers of the GSTP1 valine carriers [7,8,13,15].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, our observation of a nonsignificantly increased OS in carriers of the valine is in accordance with previous reports of an association of the GSTP1 valine allele with increased survival (progression-free survival or OS) in CRC patients in general [7], as well as in patients with metastatic CRC treated with different chemotherapeutic regimens [8--11,13], although the results were significant only in two studies [8,11]. Other studies either found no association overall or decreased survival after chemotherapy in carriers of the GSTP1 valine carriers [7,8,13,15].…”
Section: Discussionsupporting
confidence: 94%
“…Genetic variants in three GST classes have been investigated for their influence on CRC survival, but the results have been inconclusive and often nonsignificant. The GSTP1 ile105val polymorphism has been associated with an increased overall survival (OS) in White CRC patients carrying the valine allele in six studies [7][8][9][10][11][12], but two other studies found no association at all [12][13][14] or even a decreased survival [15]. In patients receiving second-line oxaliplatin treatment, the GSTP1 polymorphism has been associated with prolonged survival [8], which is biologically plausible as the GSTP1 enzyme can prevent the formation of platinum DNA adducts [3].…”
Section: Introductionmentioning
confidence: 98%
“…GSTP1 , GSTT1 and GSTM1 genotypes have been extensively studied for drug response, including oxaliplatin-based treatment (2123). A single nucleotide polymorphism at codon 105 (A>G: Ile>Val) of GSTP1 affects enzyme activity (24).…”
Section: Introductionmentioning
confidence: 99%
“…A single nucleotide polymorphism at codon 105 (A>G: Ile>Val) of GSTP1 affects enzyme activity (24). Several studies have demonstrated that among MCRC patients receiving oxaliplatin-based treatment, patients with GSTP1 -105 A/G and G/G genotypes have a more favorable outcome compared with patients with the GSTP1 -105 A/A genotype (2123). …”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that genetic variants in the MTHFR gene may modify the activity of the MTHFR enzyme, which in turn reduces the activity of MTHFR and causes an altered metabolism of folates (Stankova et al, 2008). Therefore, it was postulated that MTHFR genetic polymorphisms might influence the toxicity and clinical response of irinotecan-based chemotherapy in human cancers (Zarate et al, 2010). Currently, common polymorphisms (1298 A > C and 677 C/T) in the MTHFR gene have been reported to be closely associated with the toxicity and clinical responses of irinotecan-based chemotherapy in CRC patients (Glimelius et al, 2011;van HuisTanja et al, 2013).…”
Section: Introductionmentioning
confidence: 99%